2009
DOI: 10.1016/j.bbr.2009.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Wistar–Kyoto rats as an animal model of anxiety vulnerability: Support for a hypervigilance hypothesis

Abstract: Inbred Wistar-Kyoto (WKY) rats have been proposed as a model of anxiety vulnerability as they display behavioral inhibition and a constellation of learning and reactivity abnormalities relative to outbred Sprague-Dawley (SD) rats. Together, the behaviors of the WKY rat suggest a hypervigilant state may contribute to its anxiety vulnerability. To test this hypothesis, open-field behavior, acoustic startle, pre-pulse inhibition and timing behavior were assessed in WKY and Sprague Dawley (SD) rats. Timing behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
46
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 62 publications
12
46
2
1
Order By: Relevance
“…This result contrasts with previous studies in our laboratory Olango, 2012) and others (Braw et al, 2006;Malkesman et al, 2005;McAuley et al, 2009;Smith et al, 2016), which demonstrated that WKY rats spend significantly less time in the inner zone compared with SD rats. However, in the present study, the WKY rats spent most of the time freezing in the inner zone of the open field when compared to the SD rats.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result contrasts with previous studies in our laboratory Olango, 2012) and others (Braw et al, 2006;Malkesman et al, 2005;McAuley et al, 2009;Smith et al, 2016), which demonstrated that WKY rats spend significantly less time in the inner zone compared with SD rats. However, in the present study, the WKY rats spent most of the time freezing in the inner zone of the open field when compared to the SD rats.…”
Section: Discussioncontrasting
confidence: 99%
“…The fact that WKY rats exhibited lower locomotor activity but yet higher formalin-evoked nociceptive behaviour compared with SD rats suggests that their hyperalgesic behaviour is expressed independently of, and despite, their hypo locomotor activity and likely reflects exacerbated nociception in this inbred strain. Taken together, the results presented herein confirm that WKY rats display greater anxiety-and pain-related behaviour in line with the previous studies from our lab and others (Braw et al, 2006;Gentsch et al, 1987;Hyland et al, 2015;McAuley et al, 2009;Rea et al, 2014;Smith et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The ASR can be used to reveal differences in sensitivity (threshold to elicit a reflex response), responsivity (the magnitude of response), latency, as well as nonassociative processes of habituation, dishabituation and sensitization. We and others demonstrated that WKY rats made larger startle responses to a white noise within a wide range (92dB to 120dB) as compared to other inbred and outbred rat strains (Glowa and Hansen, 1994;McAuley et al, 2009;Servatius et al, 1998). Of 45 inbred and outbred rat strains including SD rats, male WKY rats exhibited the highest ASR magnitude when exposed to 8 trials of 110dB white noise (Glowa and Hansen, 1994).…”
Section: Arousalmentioning
confidence: 63%
“…Unlike its parent strain WIS rat, the WKY rat exhibits many unique behavioral characteristics differing from an out-bred rat strain. The most significant features are behavioral withdrawal, propensity to avoid, hyper-responsiveness to stress and hypervigilance (Drolet et al, 2002;Lemos et al, 2011;McAuley et al, 2009;Pare, 1992a;Pare, 1989b;Pare, 1992b;Pare, 1993;Solberg et al, 2001). …”
Section: Putative Animal Model For Vulnerability To Anxiety Disordersmentioning
confidence: 99%